2019
DOI: 10.12678/1089-313x.23.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Characteristics of Contemporary and Irish University-Level Student Dancers A Pilot Study

Abstract: In addition to the difficulties encountered by non-dancing university students, university-level dancers may encounter a range of challenges due to their status as aesthetic athletes. This pilot study compares the biopsychosocial characteristics of contemporary dance (CD) and Irish dance (ID) university students. CD (N = 30) and ID (N = 27) participants from institutions in Ireland and the United Kingdom were screened using a host of subjective and objective tools to establish baseline biopsychosocial characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Thus, compulsive striving often entails forms of self-objectification that can lead to lack of self-awareness, self-alienation, and to dancers isolating themselves from their social life ( van Staden et al, 2009 ). Similarly, evidence showed that these ideals and ingrained values can lead to obsessive passion, which is described as a rigid persistence to participate in dance, often resulting in dancing taking up disproportionate importance in an individual’s identity and leaving little space for other interests, decreasing their overall life quality ( Aujla et al, 2015 ; Cahalan et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, compulsive striving often entails forms of self-objectification that can lead to lack of self-awareness, self-alienation, and to dancers isolating themselves from their social life ( van Staden et al, 2009 ). Similarly, evidence showed that these ideals and ingrained values can lead to obsessive passion, which is described as a rigid persistence to participate in dance, often resulting in dancing taking up disproportionate importance in an individual’s identity and leaving little space for other interests, decreasing their overall life quality ( Aujla et al, 2015 ; Cahalan et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It appeared, for example, that not only teachers but also peers exerted pressure on dancers’ body image and perceived expectations ( Dantas et al, 2018 ). Classical ballet especially seemed irrevocably connected to deep-running traditions and a fostering of cultural and interpersonal stressors , which various participants in several studies reported to be “part of the deal” and as an aspect that is tacitly expected, accepted, and cultivated ( Benn and Walters, 2001 ; Risner, 2014 ; Cahalan et al, 2019 ; Haraldsen et al, 2019 ). Other challenges and factors, such as situational stressors , are underrepresented across the scoping review and could therefore not provide a much-needed understanding of factors such as dancers’ financial means, support systems, and environments ( Sanchez et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During adolescence, an increased predisposition is present toward short-term success despite possible long-term consequences, due to developmental cognitive processes, which, in turn, seems to be related to injuries ( van der Sluis et al, 2017 ). Within ballet, contemporary, and modern dance, a culture of dancing through pain and injuries is well known ( Luke et al, 2002 ; Gamboa et al, 2008 ; Cahalan et al, 2019 ), making it even more difficult to make the right decisions regarding your health. For instance, as stated by Rivera et al (2012) , “perceptions about how dancers are expected to work through pain play a significant role in whether they will choose to rehabilitate.” Yet, it is also acknowledged that athletes, such as elite runners, use self-regulation to keep track of their bodies, by monitoring their feelings and pain in order to achieve long-term goals ( Brick et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is only one systematic review (2013), regarding injuries in Irish dancers, that included two studies with limited quality and level of evidence [9]. Since then, there has been an increasing research regarding the epidemiology of Irish dance injuries [3,4,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%